In vitro antifungal activities of Actinomyces species isolated from soil samples against Trichophyton mentagrophytes - Nasser Keikha; Amin Ayatollahi Mousavi; gholam Hosein shahidi; Bahman Fouladi; Ali Reza Izadi (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Cutaneous infections arise from a homogeneous group of keratinophilic fungi, known as dermatophytes. Since these pathogenic dermatophytes are eukaryotes in nature, use of chemical antifungal agents for treatment may affect the host tissue cells. In this study, we aimed to evaluate the antifungal activity of Actinomyces species against Trichophyton mentagrophytes (abbreviated as T. mentagrophytes). The isolates were obtained from soil samples and identified by polymerase chain reaction (PCR) technique. Material and Methods: In total, 100 strains of Actinomyces species were isolated from soil samples in order to determine their antagonistic activities against T. mentagrophytes in Kerman, Iran. The electron microscopic study of these isolates was performed, based on the physiological properties of these antagonists (e.g., lipase, amylase, protease and chitinase), using relevant protocols. The isolates were identified using gene 16S rDNA via PCR technique. Results: Streptomyces flavogriseus, Streptomyces zaomyceticus strain xsd08149 and Streptomyces rochei were isolated and exhibited the most significant antagonistic activities against T. mentagrophytes. Images were obtained by an electron microscope and some spores, mycelia and morphology of spore chains were identified. Molecular, morphological and biochemical characteristics of these isolates were studied, using the internal 16S rDNA gene. Active isolates of Streptomyces sequence were compared to GenBank sequences. According to nucleotide analysis, isolate D5 had maximum similarity to Streptomyces flavogriseus (99%). Conclusion: The findings of this study showed that Streptomyces isolates from soil samples could exert antifungal effects on T. mentagrophytes